Growth models with oblique asymptote - Dubeau, Francois; Mir, Youness (Mathematical Modelling and Analysis, 2013)
A class of smooth functions which can be used as regression models for modelling phenomena requiring an oblique asymptote is analyzed. These types of models were defined as a product of a linear function and some well known growth models. In addition to their increasing character with an oblique asymptote, the resulting models provide curves with a single inflection point.